The influence of transformational leadership and interpersonal communication on the work motivation of employees in the Phylon Injection section at PT Adis Dimension Footwear Balaraja-Tangerang - Zakaria, Zakaria; Cahyono, Yoyok (UJoST- Universal Journal of Science and Technology, 2026)
The purpose of this study was to determine how much influence transformational leadership and interpersonal communication simultaneously have a significant effect on employee work motivation in the Injection Phylon section at PT Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method. The research sample consisted of 83 respondents. The technique used to determine the sample in this study was the simple random sampling technique.The results of this study indicate that (1) partially, transformational leadership significantly influences the work motivation of employees in the Phylon Injection section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (4.659 > 1.990) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (2) Partially, interpersonal communication significantly influences the work motivation of employees in the Phylon Injection section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (6.778> 1.990) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and work discipline significantly influence the work motivation of employees in the Phylon Injection section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (168.938>3.11) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of transformational leadership and interpersonal communication, both partially and simultaneously, have a significant influence on the work motivation of employees in the Phylon Injection section at PT Adis Dimension Footwear, Tangerang Regency.